2005
DOI: 10.1103/physrevlett.95.084502
|View full text |Cite
|
Sign up to set email alerts
|

Wind Reversals in Turbulent Rayleigh-Bénard Convection

Abstract: The phenomenon of irregular cessation and subsequent reversal of the large-scale circulation in turbulent Rayleigh-Bénard convection is theoretically analysed. The force and thermal balance on a single plume detached from the thermal boundary layer yields a set of coupled nonlinear equations, whose dynamics is related to the Lorenz equations. For Prandtl and Rayleigh numbers in the range 10 −2 ≤ Pr ≤ 10 3 and 10 7 ≤ Ra ≤ 10 12 , the model has the following features: (i) chaotic reversals may be exhibited at Ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
67
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 28 publications
2
67
1
4
Order By: Relevance
“…They have their roots in the Navier-Stokes equations and retain terms that are argued to be physically important. One of them [31] again is lacking the azimuthal degree of freedom that is so important to the LSC dynamics found in experiment. The other [32] is based on an exact solution of the Boussinesq equations in the inviscid and unforced limit, but employs physically unrealistic boundary conditions and adds dissipation a posteriori.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have their roots in the Navier-Stokes equations and retain terms that are argued to be physically important. One of them [31] again is lacking the azimuthal degree of freedom that is so important to the LSC dynamics found in experiment. The other [32] is based on an exact solution of the Boussinesq equations in the inviscid and unforced limit, but employs physically unrealistic boundary conditions and adds dissipation a posteriori.…”
Section: Introductionmentioning
confidence: 99%
“…No azimuthal degree of freedom was included, and thus only genuine reversals of the LSC (which are now known to be very rare events) could be produced. Two other models [31,32] describe the LSC with deterministic differential equations that have chaotic solutions. They have their roots in the Navier-Stokes equations and retain terms that are argued to be physically important.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, these works involve either stochasticity (e.g., "stochastic resonance" [8,13]), or low-dimensional models with noise [14,15]. Mishra et al [10] studied the large-scale modes of RBC in a cylindrical geometry and showed that the dipolar mode decreases in amplitude and the quadrupolar mode increases during the cessation-led reversals.…”
mentioning
confidence: 99%
“…Broadly, these works involve either stochasticity (e.g., "stochastic resonance" [8, 13]), or low-dimensional models with noise [14,15]. Mishra et al…”
mentioning
confidence: 99%
“…Benzi and Verzicco [9] and Sreenivasan et al [14] used stochastic resonance, while Arajuo et al [15] employed low-dimensional models with noise to explain reversals. Brown and Ahlers [3] and Mishra et al [11] showed that in a cylindrical geometry, the flow reversals are induced by a rotation or cessation of large-scale flow structures.…”
mentioning
confidence: 99%